Chất lượng thể chế và lựa chọn địa điểm đầu tư của các doanh nghiệp đa quốc gia – Bằng chứng tại Việt Nam - Huỳnh Thị Diệu , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The article assesses the influence of Vietnam’s institutional quality on the decision to choose our country as the investment location of multinational companies (MNCs) from 18 main investment partners over the 2013–2020 period. Institutional quality is measured through the World Bank's Worldwide Governance Indicators. Based on the augmented Gravity Model and Random effect regression method, the estimated results confirm the importance of the institutional environment affecting the decision to choose Vietnam as an investment location for MNCs, as 5/6 of the institutional quality indicators have significant influences. Specifically, while Control of Corruption, Political Stability and Regulatory Quality have a positive impact on attracting foreign direct investment into Vietnam, contrary to expectations when Government Effectiveness and Rule of Law have negative impacts on attracting this capital.
Keywords: Institutional quality; Investment location; Multinational company; Foreign direct investment; Vietnam